Prospects and obstacles to Algeria’s investment in renewable energies from the consumer point of view: Study a sample of consumers of electric energy in the city of Constantine - Rehailia, Seifeddine; Boudah, Abdeljalil (Dirassat Journal Economic Issue, 2017)
Many researchers consider that the renewable energiesare the energy of the future because it is available in most regions of the world and as well as permanent as long as the earth exists. in addition to that it is environmentally friendly, So currently several countries are seeking to invest in this area and help in the development of affordable technology. And Algeria is not in isolation from these developments as it has possession of natural ingredients thatwod make it a leader in this area if human and financial resources areinvested for the development of this type of energies. This paper aims to find out the prospects and obstacles in the investment of renewable energies in Algeria from the pointview of electric power consumers, with a sample of the population of the city of Constantine survey.